Establishing Your Florida Lawn - Laurie E. Trenholm (EDIS)
Revised! ENH-03, an 8-page illustrated fact sheet by L. E. Trenholm, describes the two primary methods of establishing turfgrass — seed and vegetative propagation (sodding, sprigging, and plugging) — as well as post-planting care, fertilizing, mowing, and renovation. Published by the UF Department of Environmental Horticulture, January 2010.